Ethnobotanical survey of Caralluma europaea (Guss.) N.E.Br. in the Beni Mellal - Khenifra region of Morocco - Zahir, Ilham; Errazik , Zahra; Tounssi , Siham; Hamamouch , Noureddine (Ethnobotany Research and Applications, 2026)
Background: This study forms part of the ongoing efforts to valorize Caralluma europaea, a Mediterranean species of the Apocynaceae family renowned for its therapeutic potential. An ethnobotanical survey was conducted in the Beni Mellal - Khenifra region to document its traditional uses, and possible adverse effects. Methods: A total of 352 structured questionnaires were administered through direct interviews with consumers and herbalists across rural and urban communes within the five provinces of the Beni Mellal-Khénifra region. Data on the plant’s traditional applications and associated side effects were analyzed using Microsoft Excel. Results: The study revealed that this plant is primarily used for therapeutic purposes (98%), mainly to treat diabetes (12.38%) and cysts (73.79%), particularly ovarian cysts. The most common preparation method is stem juice (55.22%), which is generally administered orally without a specific dosage, once a day (90.21%) until recovery (54.02%). More than 90% of respondents considered C. europaea to be non-toxic and expressed satisfaction following its therapeutic use. Conclusions: This study underscores the ethnomedicinal importance of C. europaea in Moroccan traditional medicine, especially for the treatment of cysts. Future pharmacological, toxicological, and phytochemical investigations are recommended to validate these traditional claims and to identify active compounds with potential anti-cyst properties and minimal adverse effects. Keywords: Beni Mellal-Khenifra, Caralluma europaea (Guss.) N.E.Br, Ethnobotanical Survey.